(untitled) (West African Journal on Sustainable Development, 2024)
The paper focused on the group therapeutic management of patients with drug misuse in a psychiatric ward. At the time of the therapeutic management, there were a total of 30 hospitalized patients in the psychiatric ward of the Kampala International University Teaching Hospital, Western Campus Ishaka Uganda. After the inclusion and exclusion check, 3 patients were excluded, and 12 patients were eligible. In Preconsent screening, 10 patients gave informed consent and 9 in post-consent screening. Nine patients were ready to participate in the group sessions. The result showed that only 5 patients completed the 5 sessions of the group therapy in psychoeducational, skill development, cognitive behavioural, support, and interpersonal process groups. The 5 patients who completed the 5 sessions were ready to leave substance abuse and adhere to their plans of action. Group therapy was effective at helping patients to overcome their addiction. The token economy was used as a behaviour modification technique to motivate and reinforce the patients to participate in group therapy. The paper recommended that patients with drug misuse should be encouraged to participate in group therapy through the behaviour reinforcement of token economy because of its efficacy in the rehabilitation of such patients.